PREVALENCE STUDIES OF PARASITE POMPHORHYNCHUS KASHMIRENSIS IN LOCAL FISH SPECIES SCHIZOTHORAX - Ali, Niamat; Nazir, Sumayya; Ganaie, Hilal Ahmad; Muzaffar, Gousia; Chishti, M. Z. (European Scientific Journal, ESJ, 2012)
ï»¿Pomphorhynchus kashmirensis is an endoparasite of fish fauna especially that of Schizothorax species. Most often they cause gastrointestinal pathology which in severe cases can even lead to fish mortality. They have been extensively studied so far as their taxonomy is concerned but their ecology has received little attention. To find out the prevalence of Pomphorhynchus kashmirensis as it forms the basic stone towards its control measures. An annual occurrence of this parasite in different Schizothorax sps of The Dal Lake and The River Jhelum has been worked out. Investigation of Pomphorhynchus kashmirensis was carried out from December 2009 to November 2010. Three species of Schizothorax viz., S. niger, S. esocinus, and S. curvifrons were collected from two study sites- The Dal Lake and The River Jhelum. A total of 363 fish specimens of Schizothorax species were assessed and out of which 203 fishes were collected and examined from Dal Lake and 160 fishes were collected and examined from River Jhelum during the present study. On examining 363 fish specimens 94 were found to harbor the Pomphorhynchus kashmirensis parasite constituting an overall prevalence of 25.89%. Out of 203 specimens examined from the Dal Lake only 42 specimens were found infected with the Pomphorhynchus kashmirensis which constitutes the prevalence of 20.68%. Similarly out of 160 specimens examined from the River Jhelum only 52 specimens were infected with the Pomphorhynchus kashmirensis which constitutes 32.5%. A seasonal cycle was witnessed with summer showing the highest prevalence of 39.622% (S. niger46.34%, S. curvifrons 31.11% and S. esocinus 30%) and least prevalence was found during the winter season 10.25%, Gender wise observations revealed that the sex wise differences were not much prominent but in most cases males 30.30% (S. niger 32.50%, S. curvifrons 27.65% and S. esocinus 28.94%) were found to be more infected than females 27.27% (S. niger 27.14%, S. curvifrons 36.61% and S. esocinus 15.78%) (S. niger 14.28 %, S. curvifrons 6.89% and S. esocinus 9.52%). The results show the dire need of the application of some suitable measures against these parasites so that our fish fauna are spared from them.